Kultivasi Budaya Pemuda Kubu dalam Hutan-hutan Dharmasraya Sumatera Barat - Ahmad Arrozy; Nenan Angenani Titis; Fuji Riang Prastowo (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
This study aims to describe changes in the culture of youth Kubu in Dharmasraya Forest, West Sumatra. Bulangan forest was a place of origin and home for the Kubu community. The expansion of the oil palm company againts Bulangan Forest caused the Kubu community to move to Padang Hilalang forest and started to develop shifting cultivation. Nomad tradition (Melangun) began to be replaced because of Kubu community loss forest as living space due to the palm oil industry mechanism. The results of the study showed that there was a change in the forests which were the native habitat of the Kubu community. It made communal compulsion that it was necessary to continue swidden agriculture. The economic transactions with the other communities are one of the accesses of the Kubu youth to interact with the outside of the forest, but at the same time seize the continuity tradition and the living space the young Kubu. This cultural research uses observational data and grounded theory methods based on the conceptualization of anthropological Kubu pioneered by Gerard Persoon (1989).